2018
DOI: 10.1096/fj.201701187r
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid synthase is required for profibrotic TGF‐β signaling

Abstract: Evidence is provided that the fibroproliferative actions of TGF-β are dependent on a metabolic adaptation that sustains pathologic growth. Specifically, profibrotic TGF-β signaling is shown to require fatty acid synthase (FASN), an essential anabolic enzyme responsible for the de novo synthesis of fatty acids. With the use of pharmacologic and genetic approaches, we show that TGF-β-stimulated FASN expression is independent of Smad2/3 and is mediated via mammalian target of rapamycin complex 1. In the absence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 79 publications
(104 reference statements)
1
41
2
Order By: Relevance
“…These alterations result in the activation of TGFβ and predispose to the development of pulmonary fibrosis . As metabolic reprograming can have a critical role in the modulation of immune checkpoint proteins and profibrotic TGFβ signaling utilizes metabolism relevant proteins including fatty acid synthase (FASN), hexokinase II (HKII), and glutaminase 1 (GLS1), we investigated the interrelation of PD‐L1 and metabolism using several metabolic enzyme inhibitors. As shown in Figure A, while PD‐L1 induction by TGFβ was independent of HKII, FASN, or GLS1 inhibition was as effective as previously reported indoleamine 2,3‐dioxygenase (IDO‐1) inhibition by INCB in preventing PD‐L1 expression in both human and murine fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
“…These alterations result in the activation of TGFβ and predispose to the development of pulmonary fibrosis . As metabolic reprograming can have a critical role in the modulation of immune checkpoint proteins and profibrotic TGFβ signaling utilizes metabolism relevant proteins including fatty acid synthase (FASN), hexokinase II (HKII), and glutaminase 1 (GLS1), we investigated the interrelation of PD‐L1 and metabolism using several metabolic enzyme inhibitors. As shown in Figure A, while PD‐L1 induction by TGFβ was independent of HKII, FASN, or GLS1 inhibition was as effective as previously reported indoleamine 2,3‐dioxygenase (IDO‐1) inhibition by INCB in preventing PD‐L1 expression in both human and murine fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
“…[38, 39] Whereas, endogenous nitrated FAs exert anti-fibrotic effects by up-regulating peroxisome proliferator-activated receptor γ (PPARγ) in human lung fibroblasts another study showed that FASN is required for pro-fibrotic TGF-β signalling. [40]…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are required to support the role of these factors in the activation of COX-2 during MDV infection. COX-2-inducing factors such as TGF-β (32), which also activates fatty acid synthesis (31, 35), might be involved in activation of COX-2 in MDV-infected cells. In fact, we have recently shown that MDV infection increases the induction of TGF-β in vivo (36); however, further studies are required to examine the role of MDV-induced TGF-β in the induction of COX-2 during MDV infection.…”
Section: Discussionmentioning
confidence: 99%